Geothermal power : technology brief - Ito, Takatsune; Ruiz, Carlos (International Renewable Energy Agency, 2017)
Geothermal power is generated from underground heat. Found around the globe and available year-round, this largely untapped renewable energy source offers the advantage of steady, predictable large-scale power generation, in comparison to the higher variability of solar and wind power. This technology brief from the International Renewable Energy Agency (IRENA) provides technical background information, analyses market potential and barriers, and offers insights for policy makers on geothermal power generation. The amount of heat within the earth's surface is estimated to contain many times more energy than all oil and gas resources worldwide. Geothermal power, therefore, offers considerable potential for growth. Increasing deployment and the opening of new markets, meanwhile, should drive down the technology's considerable upfront developments costs, further increasing the competitiveness of geothermal power. The world's installed capacity for geothermal power reached 12.7 gigawatts in 2016, with typical generation costs ranging between USD 1 870 and USD 5 050 per kilowatt. The levelised cost of electricity (LCOE) of geothermal power plants was USD 0.04-0.14 per kilowatt-hour.